Mathematics anxiety in mathematics education: a bibliometrics analysis - Wahyuni, Reny; Juniati, Dwi; Wijayanti, Pradnyo (Journal of Education and Learning (EduLearn), 2025)
This research is based on a bibliometric analysis of publications on math anxiety. It aims to analyze the distribution of the results of publications on math anxiety in the last ten years based on research trends and topics, reputable journals, influential authors, institutions, and productive countries. Scopus was used as a data collection database and was analyzed using the VOSviewer and Biblioshiny tools. The workflow carried out in this research consists of research design, data collection, data analysis, data visualization, and data interpretation. Three hundred twenty-one articles published from 2013 to 2023 were retrieved and read carefully. The results of the analysis show that many research studies on mathematics anxiety have been carried out in mathematics education, and this theme influences mathematics learning. The Journal Frontiers in Psychology is at the top, and the University of Barcelona is the most influential institution. The United States has significant relevance in this field. The results of this research also provide researchers with insight into the extent to which this field has been studied, and they can explore various alternatives to this major based on research trends and influential articles.